Ausgewählte Probleme der stilistischen Übersetzbarkeit von wissenschaftlichen Texten - Jopkiewicz, Katarzyna (Glottodidactica, 2014)
The dissemination of results has always been an important aspect of the research process. The translation plays here an increasingly important role. In view of the fact that the languages of science differ significantly, that the scientific style is simultaneously distinguished by many personal, universal and cultural features, the translation appears not to be an easy undertaking. Following the Galtung’s concept of intellectual styles we present the distinguishing features of the Teutonic and Saxonic style on the example of German and English language.